Redistributional Aspects of the Balanced-Budget Multiplier: A Comment on the Musgrave, Baumol-Peston, and Hansen Contributions - Park, Rolla Edward (The Review of Economics and Statistics, 1967)
Near the end of World War II, a number of economists advanced the famous balanced-budget multiplier theorem: an equal increase in tax collections and government expenditures will increase the national income by a like amount. The balanced-budget multiplier is equal to one. This important theorem pointed out the existence of a third road to full employment, in addition to the two already well-known (though not yet heavily traveled) deficit-increasing roads, an expenditure increase or a tax cut. Since then, the literature on the subject has concentrated on introducing qualifications into the simple balanced-budget multiplier model. The purpose of this note is to show the relationships among a number of the qualifications. These apparently unrelated qualifications will be seen to fall into place as special cases of a more general formulation. They may all be fruitfully viewed as considering redistribution among sectors of the economy having different marginal propensities to consume. A simple diagrammatic approach that emphasizes this basic similarity will be used. The same diagrammatic approach will finally be used to construct a balanced-budget multiplier model that embraces all of the redistributional qualifications already discussed plus another one of some importance.